Designing an Intellectual Capital Status Assessment Model Based on Productivity Improvement Approach: The Case of Iranian Universities - Shahin Gheyasi; Mohammad Hosseinpour; Yadolah Mehralizaedeh; Marya Nasiri (مدیریت بهره وری, 2021)
Intellectual capital refers to the body of knowledge, experience, and information that exists in an organization and is considered as intangible organizational assets and resources that can be converted to products, services, and processes to promote productivity and create values. The current applied, descriptive survey set out to investigate and analyze the main indicators and facets of intellectual capital assessment at university level through Interpretive Structural Modeling (ISM). The research data were gleaned using an interview and a questionnaire. First, the facets and indicators of intellectual capital were identified based on an extensive literature review and comparative content analyses of relevant existing studies as well as interviews with experts in the field who were selected via purposive sampling. Further, the relationships between the aspects and indicators of intellectual capital including human, structural and relational resources and indicators of intellectual capital assessment procedure at university were integratively determined and analyzed through ISM.  Finally, the main variables influencing other variables and influenced by them were identified via MICMAC analysis.  The findings identified the administration and students as independent variables with high levels of dependency and susceptibility that could be impacted by other mediating variables. Any improvement in intellectual capital at university level seem to be reliant on prerequisite modifications in these variables.